Creating a startup at a University by using Shane's theory and the entrepreneural learning model: A narrative method - R. Tri Priyono Budi Santoso; I. Wayan Ruspendi Junaedi; Sony Heru Priyanto; Donald Samuel Slamet Santoso (Journal of Innovation and Entrepreneurship, 2021)
The novelty of this research is in applying the construction of the Shane Theory and Entrepeneurial Learning Model in applying Entrepreneurship Education at a higher education institution. This study used action research by utilizing a narrative method. The business field which matched with the academic discipline as well as business interest and hobby was more successful than that which had a different prospect as a startup. Leadership, entrepreneurship, and managerial ability are the determining factors in the success of a startup company. It can delve more into the entrepreneurship process of startups to recognize opportunities to create ideas, start businesses, and develop businesses.
Keywords: 650; Entrepreneurial learning model; Narrative method; Shane theory; Startup